2-acetylphenol analogs as potent reversible monoamine oxidase inhibitors - Legoabe LJ; Petzer A; Petzer JP (Dove Medical Press, 2015)
Lesetja J Legoabe,1 Anél Petzer,1 Jacobus P Petzer1,21Centre of Excellence for Pharmaceutical Sciences, 2Department of Pharmaceutical Chemistry, School of Pharmacy, North-West University, Potchefstroom, South AfricaAbstract: Based on a previous report that substituted 2-acetylphenols may be promising leads for the design of novel monoamine oxidase (MAO) inhibitors, a series of C5-substituted 2-acetylphenol analogs (15) and related compounds (two) were synthesized and evaluated as inhibitors of human MAO-A and MAO-B. Generally, the study compounds exhibited inhibitory activities against both MAO-A and MAO-B, with selectivity for the B isoform. Among the compounds evaluated, seven compounds exhibited IC50 values <0.01 µM for MAO-B inhibition, with the most selective compound being 17,000-fold selective for MAO-B over the MAO-A isoform. Analyses of the structure–activity relationships for MAO inhibition show that substitution on the C5 position of the 2-acetylphenol moiety is a requirement for MAO-B inhibition, and the benzyloxy substituent is particularly favorable in this regard. This study concludes that C5-substituted 2-acetylphenol analogs are potent and selective MAO-B inhibitors, appropriate for the design of therapies for neurodegenerative disorders such as Parkinson’s disease.Keywords: monoamine oxidase, MAO, inhibition, 2-acetylphenol, structure–activity relationship